2014
DOI: 10.1093/infdis/jiu650
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccine Effectiveness in Households With Children During the 2012-2013 Season: Assessments of Prior Vaccination and Serologic Susceptibility

Abstract: Prior vaccination appears to modify VE by both residual protection and reduced vaccine response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
110
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(126 citation statements)
references
References 20 publications
13
110
2
1
Order By: Relevance
“…Eighteen studies met the eligibility criteria [4,13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Of these, one study was restricted to hospitalized patients and was therefore excluded from the meta-analysis [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen studies met the eligibility criteria [4,13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Of these, one study was restricted to hospitalized patients and was therefore excluded from the meta-analysis [31].…”
Section: Resultsmentioning
confidence: 99%
“…Another study at the University of Michigan found blunting of the H3N2 vaccine response in a cohort study with 321 households (1426 members) during the 2012-2013 season [21]. Subjects with any vaccine exposure had higher titers than those who were unvaccinated in both 2012-2013 and the prior season.…”
Section: Michigan Household Cohort Studymentioning
confidence: 97%
“…Current season influenza VE has been suggested to vary by prior season influenza vaccine history [34][35][36]. Our study would benefit from having taken prior season influenza vaccination into account in the analysis, however, sample size for stratification by receipt of previous season vaccination is still small despite the five year pooling.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-derived samples of influenza A virus were collected as part of the Household Influenza Vaccine Effectiveness (HIVE) study (39,40) and kindly provided by Arnold S. Monto and colleagues at the University of Michigan School of Public Health. The HIVE study was approved by the Institutional Review Board at the University of Michigan, and all subjects provided informed consent.…”
Section: Methodsmentioning
confidence: 99%